A new class of prophylactic metallo-antibiotic possessing potent anti-cancer and anti-microbial properties. Issue 24 (4th April 2019) - Ude, Ziga; Kavanagh, Kevin; Twamley, Brendan; Pour, Milan; Gathergood, Nicholas; Kellett, Andrew; Marmion, Celine J.
Abstract : A family of metallo-antibiotics of general formula [Cu(N, N)(CipA)Cl] where N, N is a phenanthrene ligand and CipA is a derivative of the clinically used fluoroquinolone antibiotic ciprofloxacin – targeting immunocompromised cancer patients undergoing chemotherapy. Abstract : Immunocompromised cancer patients are often at high risk of developing infections. Standard infection control measures are required to prevent the onset of infection but, under some circumstances, antimicrobial prophylaxis is necessary. We have developed a family of innovative metallo-antibiotics of general formula [Cu(N, N)(CipA)Cl] where N, N represents a phenanthrene ligand and CipA stands for a derivative of the clinically used fluoroquinolone antibiotic ciprofloxacin. The X-ray crystal structure of one member from this family, [Cu(phen)(CipA)Cl] (where phen is 1, 10-phenanthroline), is also reported. These complexes combine into one drug entity a Cu-N, N-framework with DNA binding and DNA oxidant properties and an antibiotic derivative with known anti-proliferative and anti-microbial activities. The complexes were all found to exhibit excellent DNA recognition with binding affinity of lead agents in the order of ∼10 7 M(bp) −1 . Biophysical studies involving calf thymus DNA indicate the complexes intercalate or semi-intercalate DNA via the minor groove. All complexes exhibited excellent nuclease activity with DNA strand scission being mediated predominantly via superoxide and hydroxyl radicals. The complexes were found to have promising anti-proliferative effects against a human breast adenocarcinoma cell line (MCF-7) and a human prostate carcinoma cell line (DU145) with low micromolar and, in some cases, nanomolar cytotoxicities observed. Selective targeting of Gram positive bacteria was also identified by this complex class with one lead compound having an order of magnitude greater potency against Methicillin-resistant S. aureus (MRSA) as compared to the CipA ligand. Importantly, from a clinical stand point, these complexes were also found to be well tolerated in an in vivo Galleria mellonella larvae model, which has both functional and structural similarities to that of the innate immune system of mammals.